Sinergi Pengelolaan Lingkungan Hidup Melalui Sistem Pengendalian Hama Terpadu (Kasus Pada Usahatani Bawang Merah) - Astuti, Andjar; Krisdianto, Nanang; Nurjannah, Ayu (JURNAL AGRIBISNIS TERPADU, 2018)
Environmental natural resources prepared by non-biological or abiotic, biotic or biological resources, and human resources shared resources are merged into artificial cultural resources. For that management needs to be done in synergy between these three components, and is expected to impact positively on communities around the neighborhood in particular and society in general, which ultimately is slowly but surely will be able to improve the welfare of the community. Forms of Environmental Management conducted in synergy can be the technology im-plementation of Integrated Pest Management (IPM), which combine some way to control the economic, ecological and social accountability. This research implement IPM on a red onion farming, because farming is a lot to experience problems, including the attack Pests and Diseases. The purpose of research is to analyze the technical and economic success of the implementation of IPM. In District Babakan, Cirebon. Respondents with census method making as many as 45 people, data used are primary data and secondary data, the data is tabulated and analyzed quantitatively. Results of the analysis showed that the red onion farming implement IPM technology is more advantageous and more efficient, when compared to conventional farming is done.